Combined targeting poly (ADP-ribose) polymerase and receptor tyrosine kinase inhibits ovarian clear cell carcinoma progression through disrupted ribosome biogenesis - Chiao-Yun Lin; An-Shine Chao; Angel Chao; Ren-Chin Wu; Alice L. Yu; Chiung-Hui Fu; Yu-Chuan Teng; Ruby Yun-Ju Huang; Chyong-Huey Lai (Journal of Molecular Medicine, 2026)

3-OH-FA- and branched GDGT-based temperature calibrations from a transect of lakes in the eastern USA - Changhai Hou; Michael L. Griffiths; Alice Hardman; Osamu Seki; Aifeng Zhou; Sarah Greene; Elizabeth W. Patterson; Roland Indriksons; Sabrina Ryan; Michael DaSilva; Matthew Allison; Lin Chen; et al. (Organic Geochemistry, 2026)

Contributions of previous whole-brain radiation therapy, cumulative intracranial tumor volume, and repeat radiosurgery to adverse radiation effects following stereotactic radiosurgery for brain metastasis - Ali A. Alattar; Jiri Bartek; Alice Lin; Carlin Chuck; Hsien-Chung Chen; Giovanni Kozel; Sharona Ben-Haim; Clark C. Chen (Clinical & Experimental Metastasis, 2026)

The Interplay of Traits, Phylogeny and Abundance Shapes Spatial Mammal Diversity Patterns - Kay Zin Than; Alice C. Hughes; Lin Wang; Zaw Zaw; Rui‐Chang Quan (Global Ecology and Biogeography, 2025)
Aim Terrestrial mammal communities are crucial indicators of tropical ecosystem health and sustainability. However, the role of shared species responses driven by functional traits and phylogenetic relatedness in shaping community assembly remains underexplored for identifying conservation hotspots. Spatial predictions of species diversity also remain limited by approaches that fail to jointly account for species occupancy and abundance. This study evaluates trait‐ and phylogeny‐informed environmental filtering in structuring mammal communities and maps spatial diversity patterns by integrating species occupancy and abundance across spatial–temporal scales. Ultimately, areas of high mammal diversity reflecting underlying assembly processes are identified to guide regional conservation planning. Location Myanmar and China. Time Period 2015–2021. Major Taxa Studied Terrestrial mammals. Methods We deployed 936 camera traps over 6 years across Upper Myanmar and Xishuangbanna, China, using a nested sampling design that ensured robust spatial–temporal replication, and analysed the data using community hierarchical models. Results Climate and habitat factors predominantly drive species richness, while traits and phylogenetic relatedness jointly shape distinct community patterns. Seasonal variation in local diversity underscores the role of environmental filtering in structuring mammal communities across space and time. Large‐bodied omnivores favour stable temperature niches, whereas reduced precipitation filters communities towards wide‐ranging mammals. Anthropogenic disturbances and forest cover loss alter community structure, diminishing the prevalence of carnivorous traits. Predictive community maps with uncertainty estimates guide future survey efforts through a more integrative, data‐informed approach to regional planning. Main Conclusions This study presents a novel framework for improving climate‐ and habitat‐based biodiversity models by integrating trait‐ and phylogeny‐informed assembly processes with abundance‐based predictions across suitable habitats. The findings, including phylogenetically clustered niches in Cervidae and Felidae, suggest that shared evolutionary adaptations, such as temperature tolerance in ungulates and disturbance tolerance in carnivores, shape community assembly under varying environmental pressures and can inform spatial conservation prioritisation.

Variation in uptake of sodium glucose cotransporter 2 inhibitors and glucagon-like peptide-1 receptor analogues in adults with type 2 diabetes at high cardiovascular risk - Juliana de Oliveira Costa; Jialing Lin; Tamara Y. Milder; Alys Havard; Jerry R. Greenfield; Richard O. Day; Brendon L. Neuen; Alice A. Gibson; Jedidiah I. Morton; Julian W. Sacre; Sallie-Anne Pearson; Michael O. Falster (European Journal of Clinical Pharmacology, 2025)
Purpose We quantified variation in the uptake of sodium-glucose co-transporter 2 inhibitors (SGLT2i) and glucagon-like peptide-1 receptor analogues (GLP-1RA) across sociodemographic, behavioural and clinical characteristics of people with type 2 diabetes (T2D) at high cardiovascular risk. Methods We used the 45 and Up Study survey data (2018–2020) linked to dispensing and service claims for 10,171 people with T2D (56% male, median age of 72 years, median diabetes duration of 11 years). We calculated the prevalence of GLP-1RA and SGLT2i use within 1 year and used logistic regressions to assess associations with each participant characteristic. Results We found that 2270 (22.3%) people with T2D used SGLT2i and 679 (6.7%) used GLP-1RA. Use of these medicines was higher in people diagnosed with diabetes for a longer period, a high number of comorbidities and survey year, decreased in older people, and varied by sex. After adjusting for these factors, utilisation of these medicines was lower among people who consume alcohol (versus non-drinkers) and higher among those with overweight or obesity. SGLT2i use was also higher in people who were less physically active or had established cardiovascular disease and lower in people with anxiety or depression. GLP-1RA use was higher among people with poorer health and lower in people born outside Australia/New Zealand. Conclusion Prevalent use of SGLT2i and GLP-1RA was suboptimal and varied across clinical characteristics and behavioural risk factors. While some variation reflects complexities in prescribing for this older population, there remains opportunity for optimised prescribing within this high-risk population.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Multiple hydrothermal events at martian surface revealed by H and Cl isotope systematics of melt inclusions and hydrous minerals from chassignite NWA 2737 - Sen Hu; Mahesh Anand; Ian A. Franchi; Xuchao Zhao; Alice Stephant; Magali Bonifacie; Huicun He; Wei Yang; Jialong Hao; Yangting Lin (Earth and Planetary Science Letters, 2024)

Artificial intelligence improves risk prediction in cardiovascular disease - Achamyeleh Birhanu Teshale; Htet Lin Htun; Mor Vered; Alice J. Owen; Joanne Ryan; Andrew Tonkin; Rosanne Freak-Poli (GeroScience, 2024)

Label analysis and molecular identification of Japanese Seafood Products purchased on Chinese e-commerce - Xia Zhang; Chiara Malloggi; Alice Giusti; Weide Deng; Zhenzhu Sun; Yuan Li; Jing Guo; Hongyuan Peng; Lara Tinacci; Lin Gao; Andrea Armani; Jing Wen (Food Control, 2024)

Large-eddy simulations on pollutant reduction effects of road-center hedge and solid barriers in an idealized street canyon - Chao Lin; Ryozo Ooka; Hideki Kikumoto; Cédric Flageul; Youngseob Kim; Yunyi Wang; Alice Maison; Yang Zhang; Karine Sartelet (Building and Environment, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Packaging contaminants in former food products: Using Fourier Transform Infrared Spectroscopy to identify the remnants and the associated risks - Sharon Mazzoleni; Stefano Magni; Marco Tretola; Alice Luciano; Luca Ferrari; Cristian Edoardo Maria Bernardi; Peng Lin; Matteo Ottoboni; Andrea Binelli; Luciano Pinotti (Journal of Hazardous Materials, 2023)

Chromatin modifiers: A new class of pollutants with potential epigenetic effects revealed by in vitro assays and transcriptomic analyses - Chi Tim Leung; Yi Yang; Ting Fung Chan; Xiao Lin; Alice Sze Tsai Wong; Wing Yee Lui; Karen Wing Yee Yuen; Richard Yuen Chong Kong; Keng Po Lai; Rudolf Shiu Sun Wu (Toxicology, 2023)

The Effects of Limosilactobacillus reuteri LR-99 Supplementation on Body Mass Index, Social Communication, Fine Motor Function, and Gut Microbiome Composition in Individuals with Prader–Willi Syndrome: a Randomized Double-Blinded Placebo-Controlled Trial - Xue-Jun Kong; Kevin Liu; Patrick Zhuang; Ruiyi Tian; Siyu Liu; Cullen Clairmont; Xiaojing Lin; Hannah Sherman; Junli Zhu; Yelan Wang; Michelle Fong; Alice Li; et al. (Probiotics and Antimicrobial Proteins, 2021)
Prader–Willi syndrome (PWS) is a rare genetic disorder associated with developmental delay, obesity, and neuropsychiatric comorbidities. Limosilactobacillus reuteri ( Lactobacillus reuteri , Lact. reuteri ) has demonstrated anti-obesity and anti-inflammatory effects in previous studies. In the present study, we aim to evaluate the effects of Lact. reuteri supplementation on body mass index (BMI), social behaviors, and gut microbiota in individuals with PWS. We conducted a 12-week, randomized, double-blind, placebo-controlled trial in 71 individuals with PWS aged 6 to 264 months (64.4 ± 51.0 months). Participants were randomly assigned to either receive daily Lact. reuteri LR-99 probiotic (6 × 10 10 colony forming units) or a placebo sachet. Groupwise differences were assessed for BMI, ASQ-3, and GARS-3 at baseline, 6 weeks, and 12 weeks into treatment. Gut microbiome data was analyzed with the QIIME2 software package, and predictive functional profiling was conducted with PICRUSt-2. We found a significant reduction in BMI for the probiotic group at both 6 weeks and 12 weeks relative to the baseline ( P < 0.05). Furthermore, we observed a significant improvement in social communication and interaction, fine motor function, and total ASQ-3 score in the probiotics group compared to the placebo group ( P < 0.05). Altered gut microbiota was observed in the probiotic group to favor weight loss and improve gut health. The findings suggest a novel therapeutic potential for Lact. reuteri LR-99 probiotic to modulate BMI, social behaviors, and gut microbiota in Prader–Willi syndrome patients, although further investigation is warranted. Trial registration Chinese Clinical Trial Registry: ChiCTR1900022646

Optic lobe organization in stomatopod crustacean species possessing different degrees of retinal complexity - Chan Lin; Alice Chou; Thomas W. Cronin (Journal of Comparative Physiology A, 2020)

Simplified Tai Chi 6-Form Apparatus for Balance in Elderly People with Alzheimer’s Disease - Yin-Chou Lin; Wen-Chuin Hsu; Chien-Hung Chen; Chai-Wei Wang; Katie Pei-Hsuan Wu; Alice M. K. Wong (Journal of Medical and Biological Engineering, 2019)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Different responses of influenza epidemic to weather factors among Shanghai, Hong Kong, and British Columbia - Xi-Ling Wang; Lin Yang; Dai-Hai He; Alice PY Chiu; Kwok-Hung Chan; King-Pan Chan; Maigeng Zhou; Chit-Ming Wong; Qing Guo; Wenbiao Hu (International Journal of Biometeorology, 2017)

Home paint exposures and risk of childhood acute lymphoblastic leukemia: findings from the Childhood Leukemia International Consortium - Helen D. Bailey; Catherine Metayer; Elizabeth Milne; Eleni Th. Petridou; Claire Infante-Rivard; Logan G. Spector; Jacqueline Clavel; John D. Dockerty; Luoping Zhang; Bruce K. Armstrong; Jérémie Rudant; Lin Fritschi; et al. (Cancer Causes & Control, 2015)

Preclinical Pharmacokinetic/Pharmacodynamic Modeling and Simulation in the Pharmaceutical Industry: An IQ Consortium Survey Examining the Current Landscape - Edgar Schuck; Tonika Bohnert; Arijit Chakravarty; Valeriu Damian-Iordache; Christopher Gibson; Cheng-Pang Hsu; Tycho Heimbach; Anu Shilpa Krishnatry; Bianca M Liederer; Jing Lin; Tristan Maurer; Jerome T Mettetal; et al. (The AAPS Journal, 2015)

Parental occupational paint exposure and risk of childhood leukemia in the offspring: findings from the Childhood Leukemia International Consortium - Helen D. Bailey; Lin Fritschi; Catherine Metayer; Claire Infante-Rivard; Corrado Magnani; Eleni Petridou; Eve Roman; Logan G. Spector; Peter Kaatsch; Jacqueline Clavel; Elizabeth Milne; John D. Dockerty; et al. (Cancer Causes & Control, 2014)

Effects of Parkinson’s disease on optic flow perception for heading direction during navigation - Cheng-Chieh Lin; Robert C. Wagenaar; Daniel Young; Elliot L. Saltzman; Xiaolin Ren; Sandy Neargarder; Alice Cronin-Golomb (Experimental Brain Research, 2014)

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

HOXB13 is a susceptibility gene for prostate cancer: results from the International Consortium for Prostate Cancer Genetics (ICPCG) - Jianfeng Xu; Ethan M. Lange; Lingyi Lu; Siqun L. Zheng; Zhong Wang; Stephen N. Thibodeau; Lisa A. Cannon-Albright; Craig C. Teerlink; Nicola J. Camp; Anna M. Johnson; Kimberly A. Zuhlke; Janet L. Stanford; et al. (Human Genetics, 2013)

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

Relationships between physiological responses and presyncope symptoms during tilting up in patients with spinal cord injury - David S. Liu; Walter H. Chang; Alice M. K. Wong; Shih-Ching Chen; Kang-Ping Lin; Chien-Hung Lai (Medical & Biological Engineering & Computing, 2008)

Development of a biofeedback tilt-table for investigating orthostatic syncope in patients with spinal cord injury - David S. Liu; Walter H. Chang; Alice M. K. Wong; Shih-Ching Chen; Kang-Ping Lin; Chien-Hung Lai (Medical & Biological Engineering & Computing, 2007)

Rapid Evolution, Genetic Variations, and Functional Association of the Human Spermatogenesis-Related Gene NYD-SP12 - Qü Zhang; Feng Zhang; Xiao-hua Chen; Yin-qiu Wang; Wei-qi Wang; Alice A. Lin; Luca L. Cavalli-Sforza; Li Jin; Ran Huo; Jia-hao Sha; Zheng Li; Bing Su (Journal of Molecular Evolution, 2007)

Molecular Evolution of CXCR1, a G Protein-Coupled Receptor Involved in Signal Transduction of Neutrophils - Ying Liu; Su Yang; Alice A. Lin; Luca L. Cavalli-Sforza; Bing Su (Journal of Molecular Evolution, 2005)

Excavating Y-chromosome haplotype strata in Anatolia - Cengiz Cinnioglu; Roy King; Toomas Kivisild; Ersi Kalfoglu; Sevil Atasoy; Gianpiero L. Cavalleri; Anita S. Lillie; Charles C. Roseman; Alice A. Lin; Kristina Prince; Peter J. Oefner; Peidong Shen; et al. (Human Genetics, 2004)

In vitro and in vivo evaluations of biodegradable implants for hormone replacement therapy: Effect of system design and PK-PD relationship - Senshang Lin; Pi-Yun Chao; Yie W. Chien; Amyn Sayani; Sandeep Kumar; Michelle Mason; Thomas West; Alice Yang; Donald Monkhouse (AAPS PharmSciTech, 2001)